Evaluation of factors that influence the L-glutamic and γ-aminobutyric acid production during Hericium erinaceus fermentation by lactic acid bacteria - Sasimar Woraharn (2018)
© 2015 The Author(s). Published by Taylor & Francis. Fermented plant beverages (FPBs) are non-alcoholic and are produced by lactic acid bacteria (LAB) with different edible plant sources. Owing to the lack of a detailed study on fermented Hericium erinaceus with LAB, the current study was employed to exploit and optimize the fermentation condition for the production of L-glutamic acid (GA)- and γ-aminobutyric acid (GABA)-rich fermented H. erinaceus beverage by Lactobacillus brevis HP2 and Lactobacillus fermentum HP3, respectively. Box-Behnken design (BBD) for response surface methodology was employed with cofactor, pH and temperature as independent variables. The results suggested that L. brevis HP2 and L. fermentum HP3 are good starter cultures for H. erinaceus fermentation with enriched GA and GABA production. In this case, GA production was significantly influenced by K2HPO4, pH and temperature whereas GABA production was significantly influenced by pH and temperature. Further thorough and fine optimization is required to fabricate high-quality fermented drinks with low cost.